My three book - Moncure, Jane Belk (Elgin, Ill : The Child's World, Inc, 1985)
Little Three introduces the concepts of "three" and counting by encountering trios of baskets, pigs, dancing mice, and other objects and animals
Keywords: Three (The number) -- Juvenile literature; Number Concept; Counting